My father's tears and other stories [compact disc, unabridged] - Updike, John (Brilliance Audio, Inc., 2009)
In the late John Updike's final collection of short fiction he mingles narratives of his native Pennsylvania with stories of New England suburbia and of foreign travel, exploring the American experience from the Depression to the aftermath of 9/11.